2007
DOI: 10.1103/physrevd.76.031501
|View full text |Cite
|
Sign up to set email alerts
|

Abelian dominance and the dual Meissner effect in local unitary gauges in SU(2) gluodynamics

Abstract: Performing highly precise Monte-Carlo simulations of SU(2) gluodynamics, we observe for the first time Abelian dominance in the confining part of the static potential in local unitary gauges such as the F12 gauge. We also study the flux-tube profile between the quark and antiquark in these local unitary gauges and find a clear signal of the dual Meissner effect. The Abelian electric field is found to be squeezed into a flux tube by the monopole supercurrent. This feature is the same as that observed in the non… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 37 publications
8
26
0
Order By: Relevance
“…Numerically, an Abelian projection in non-local gauges such as the maximally Abelian (MA) gauge [7,8] has been found to support the Abelian confinement scenario beautifully [9,10]. Very recently, the present authors have shown that the Abelian dominance and the dual Meissner effect are observed clearly also in local unitary gauges such as F12 and Polyakov (PL) gauges [11]. These results strongly suggest that the Abelian confinement mechanism is gauge-independent.…”
Section: Introductionsupporting
confidence: 65%
“…Numerically, an Abelian projection in non-local gauges such as the maximally Abelian (MA) gauge [7,8] has been found to support the Abelian confinement scenario beautifully [9,10]. Very recently, the present authors have shown that the Abelian dominance and the dual Meissner effect are observed clearly also in local unitary gauges such as F12 and Polyakov (PL) gauges [11]. These results strongly suggest that the Abelian confinement mechanism is gauge-independent.…”
Section: Introductionsupporting
confidence: 65%
“…This idea of Abelian dominance has recently been verified by gauge fixing and Abelian projection [35] and also by constructing semilocal models in Extended Abelian Higgs model (EAH-model) [36,37]. The same idea has been used, more recently, in connection with the dual Meissner effect in local unitary gauges in SU(2) gluo-dynamics [38] and also with confining ensemble of dyons [39] and dual superconductivity in Yang-Mills theories [40].…”
Section: Discussionmentioning
confidence: 93%
“…The similar result has also been obtained more recently in a dual superconductivity model [14] which places the Y -M vacuum close to the border between Type-I and Type-II superconductors and marginally on the Type-II side. The same idea of Abelian dominance has been used more recently in connection with the dual Meissner effect in local unitary gauges in SU(2) gluodynamic [49] and also with confining ensemble of dyons [50] and dual superconductivity in Yang-Mills theories [14].…”
Section: Discussionmentioning
confidence: 93%